Industrial Clusters and Economic Performance in Brazil - Jose Claudio Pires; Túlio Cravo; Simon Lodato; Caio Piza (Inter-American Development Bank (IDB), 2013)
Industrial clusters, which are commonly targeted to receive financial support allocated to locally based development projects, are seen as an effective industrial policy tool for improving productivity and generating employment. Nevertheless, identifying clusters and assessing their economic performance is a challenge for policymakers. This paper aims to address this challenge by identifying the location of clusters based on neighbor relationships and specialization in Brazil and providing some insights on their effects on employment generation. The paper uses both Location Quotient and Local Indicator of Spatial Association to identify potential clusters in 27 industrial sectors in 5564 Brazilian municipalities. In addition, it uses annual municipal panel data for 2006-2009 to assess whether the presence of potential clusters is correlated with employment generation. The results show that clusters located in municipalities whose neighbors have similar industrial structures perform better than those that present industry specialization only.
hdl:11319/4771
Keywords: C0; R11; R12; 330; Industrial cluster; regional economic development; spatial dependence